Mercurial > hg > Members > kono > Proof > ZF-in-agda
comparison src/ODUtil.agda @ 431:a5f8084b8368
reorganiztion for apkg
author | Shinji KONO <kono@ie.u-ryukyu.ac.jp> |
---|---|
date | Mon, 21 Dec 2020 10:23:37 +0900 |
parents | |
children | 364d738f871d |
comparison
equal
deleted
inserted
replaced
430:28c7be8f252c | 431:a5f8084b8368 |
---|---|
1 {-# OPTIONS --allow-unsolved-metas #-} | |
2 open import Level | |
3 open import Ordinals | |
4 module ODUtil {n : Level } (O : Ordinals {n} ) where | |
5 | |
6 open import zf | |
7 open import Data.Nat renaming ( zero to Zero ; suc to Suc ; ℕ to Nat ; _⊔_ to _n⊔_ ) | |
8 open import Relation.Binary.PropositionalEquality hiding ( [_] ) | |
9 open import Data.Nat.Properties | |
10 open import Data.Empty | |
11 open import Relation.Nullary | |
12 open import Relation.Binary hiding ( _⇔_ ) | |
13 | |
14 open import logic | |
15 open import nat | |
16 | |
17 open Ordinals.Ordinals O | |
18 open Ordinals.IsOrdinals isOrdinal | |
19 open Ordinals.IsNext isNext | |
20 import OrdUtil | |
21 open OrdUtil O | |
22 | |
23 import OD | |
24 open OD O | |
25 open OD.OD | |
26 open ODAxiom odAxiom | |
27 | |
28 open HOD | |
29 open _⊆_ | |
30 open _∧_ | |
31 open _==_ | |
32 | |
33 cseq : HOD → HOD | |
34 cseq x = record { od = record { def = λ y → odef x (osuc y) } ; odmax = osuc (odmax x) ; <odmax = lemma } where | |
35 lemma : {y : Ordinal} → def (od x) (osuc y) → y o< osuc (odmax x) | |
36 lemma {y} lt = ordtrans <-osuc (ordtrans (<odmax x lt) <-osuc ) | |
37 | |
38 | |
39 pair-xx<xy : {x y : HOD} → & (x , x) o< osuc (& (x , y) ) | |
40 pair-xx<xy {x} {y} = ⊆→o≤ lemma where | |
41 lemma : {z : Ordinal} → def (od (x , x)) z → def (od (x , y)) z | |
42 lemma {z} (case1 refl) = case1 refl | |
43 lemma {z} (case2 refl) = case1 refl | |
44 | |
45 pair-<xy : {x y : HOD} → {n : Ordinal} → & x o< next n → & y o< next n → & (x , y) o< next n | |
46 pair-<xy {x} {y} {o} x<nn y<nn with trio< (& x) (& y) | inspect (omax (& x)) (& y) | |
47 ... | tri< a ¬b ¬c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (sym eq1) (osuc<nx y<nn)) ho< | |
48 ... | tri> ¬a ¬b c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (sym eq1) (osuc<nx x<nn)) ho< | |
49 ... | tri≈ ¬a b ¬c | record { eq = eq1 } = next< (subst (λ k → k o< next o ) (omax≡ _ _ b) (subst (λ k → osuc k o< next o) b (osuc<nx x<nn))) ho< | |
50 | |
51 -- another form of infinite | |
52 -- pair-ord< : {x : Ordinal } → Set n | |
53 pair-ord< : {x : HOD } → ( {y : HOD } → & y o< next (odmax y) ) → & ( x , x ) o< next (& x) | |
54 pair-ord< {x} ho< = subst (λ k → & (x , x) o< k ) lemmab0 lemmab1 where | |
55 lemmab0 : next (odmax (x , x)) ≡ next (& x) | |
56 lemmab0 = trans (cong (λ k → next k) (omxx _)) (sym nexto≡) | |
57 lemmab1 : & (x , x) o< next ( odmax (x , x)) | |
58 lemmab1 = ho< | |
59 | |
60 trans-⊆ : { A B C : HOD} → A ⊆ B → B ⊆ C → A ⊆ C | |
61 trans-⊆ A⊆B B⊆C = record { incl = λ x → incl B⊆C (incl A⊆B x) } | |
62 | |
63 refl-⊆ : {A : HOD} → A ⊆ A | |
64 refl-⊆ {A} = record { incl = λ x → x } | |
65 | |
66 od⊆→o≤ : {x y : HOD } → x ⊆ y → & x o< osuc (& y) | |
67 od⊆→o≤ {x} {y} lt = ⊆→o≤ {x} {y} (λ {z} x>z → subst (λ k → def (od y) k ) &iso (incl lt (d→∋ x x>z))) | |
68 | |
69 subset-lemma : {A x : HOD } → ( {y : HOD } → x ∋ y → (A ∩ x ) ∋ y ) ⇔ ( x ⊆ A ) | |
70 subset-lemma {A} {x} = record { | |
71 proj1 = λ lt → record { incl = λ x∋z → proj1 (lt x∋z) } | |
72 ; proj2 = λ x⊆A lt → ⟪ incl x⊆A lt , lt ⟫ | |
73 } | |
74 | |
75 | |
76 ω<next-o∅ : {y : Ordinal} → infinite-d y → y o< next o∅ | |
77 ω<next-o∅ {y} lt = <odmax infinite lt | |
78 | |
79 nat→ω : Nat → HOD | |
80 nat→ω Zero = od∅ | |
81 nat→ω (Suc y) = Union (nat→ω y , (nat→ω y , nat→ω y)) | |
82 | |
83 ω→nato : {y : Ordinal} → infinite-d y → Nat | |
84 ω→nato iφ = Zero | |
85 ω→nato (isuc lt) = Suc (ω→nato lt) | |
86 | |
87 ω→nat : (n : HOD) → infinite ∋ n → Nat | |
88 ω→nat n = ω→nato | |
89 | |
90 ω∋nat→ω : {n : Nat} → def (od infinite) (& (nat→ω n)) | |
91 ω∋nat→ω {Zero} = subst (λ k → def (od infinite) k) (sym ord-od∅) iφ | |
92 ω∋nat→ω {Suc n} = subst (λ k → def (od infinite) k) lemma (isuc ( ω∋nat→ω {n})) where | |
93 lemma : & (Union (* (& (nat→ω n)) , (* (& (nat→ω n)) , * (& (nat→ω n))))) ≡ & (nat→ω (Suc n)) | |
94 lemma = subst (λ k → & (Union (k , ( k , k ))) ≡ & (nat→ω (Suc n))) (sym *iso) refl | |
95 | |
96 pair1 : { x y : HOD } → (x , y ) ∋ x | |
97 pair1 = case1 refl | |
98 | |
99 pair2 : { x y : HOD } → (x , y ) ∋ y | |
100 pair2 = case2 refl | |
101 | |
102 single : {x y : HOD } → (x , x ) ∋ y → x ≡ y | |
103 single (case1 eq) = ==→o≡ ( ord→== (sym eq) ) | |
104 single (case2 eq) = ==→o≡ ( ord→== (sym eq) ) | |
105 | |
106 open import Relation.Binary.HeterogeneousEquality as HE using (_≅_ ) | |
107 -- postulate f-extensionality : { n m : Level} → HE.Extensionality n m | |
108 | |
109 ω-prev-eq1 : {x y : Ordinal} → & (Union (* y , (* y , * y))) ≡ & (Union (* x , (* x , * x))) → ¬ (x o< y) | |
110 ω-prev-eq1 {x} {y} eq x<y = eq→ (ord→== eq) {& (* y)} (λ not2 → not2 (& (* y , * y)) | |
111 ⟪ case2 refl , subst (λ k → odef k (& (* y))) (sym *iso) (case1 refl)⟫ ) (λ u → lemma u ) where | |
112 lemma : (u : Ordinal) → ¬ def (od (* x , (* x , * x))) u ∧ def (od (* u)) (& (* y)) | |
113 lemma u t with proj1 t | |
114 lemma u t | case1 u=x = o<> (c<→o< {* y} {* u} (proj2 t)) (subst₂ (λ j k → j o< k ) | |
115 (trans (sym &iso) (trans (sym u=x) (sym &iso)) ) (sym &iso) x<y ) -- x ≡ & (* u) | |
116 lemma u t | case2 u=xx = o<¬≡ (lemma1 (subst (λ k → odef k (& (* y)) ) (trans (cong (λ k → * k ) u=xx) *iso ) (proj2 t))) x<y where | |
117 lemma1 : {x y : Ordinal } → (* x , * x ) ∋ * y → x ≡ y -- y = x ∈ ( x , x ) = u | |
118 lemma1 (case1 eq) = subst₂ (λ j k → j ≡ k ) &iso &iso (sym eq) | |
119 lemma1 (case2 eq) = subst₂ (λ j k → j ≡ k ) &iso &iso (sym eq) | |
120 | |
121 ω-prev-eq : {x y : Ordinal} → & (Union (* y , (* y , * y))) ≡ & (Union (* x , (* x , * x))) → x ≡ y | |
122 ω-prev-eq {x} {y} eq with trio< x y | |
123 ω-prev-eq {x} {y} eq | tri< a ¬b ¬c = ⊥-elim (ω-prev-eq1 eq a) | |
124 ω-prev-eq {x} {y} eq | tri≈ ¬a b ¬c = b | |
125 ω-prev-eq {x} {y} eq | tri> ¬a ¬b c = ⊥-elim (ω-prev-eq1 (sym eq) c) | |
126 | |
127 ω-∈s : (x : HOD) → Union ( x , (x , x)) ∋ x | |
128 ω-∈s x not = not (& (x , x)) ⟪ case2 refl , subst (λ k → odef k (& x) ) (sym *iso) (case1 refl) ⟫ | |
129 | |
130 ωs≠0 : (x : HOD) → ¬ ( Union ( x , (x , x)) ≡ od∅ ) | |
131 ωs≠0 y eq = ⊥-elim ( ¬x<0 (subst (λ k → & y o< k ) ord-od∅ (c<→o< (subst (λ k → odef k (& y )) eq (ω-∈s y) ))) ) | |
132 | |
133 nat→ω-iso : {i : HOD} → (lt : infinite ∋ i ) → nat→ω ( ω→nat i lt ) ≡ i | |
134 nat→ω-iso {i} = ε-induction {λ i → (lt : infinite ∋ i ) → nat→ω ( ω→nat i lt ) ≡ i } ind i where | |
135 ind : {x : HOD} → ({y : HOD} → x ∋ y → (lt : infinite ∋ y) → nat→ω (ω→nat y lt) ≡ y) → | |
136 (lt : infinite ∋ x) → nat→ω (ω→nat x lt) ≡ x | |
137 ind {x} prev lt = ind1 lt *iso where | |
138 ind1 : {ox : Ordinal } → (ltd : infinite-d ox ) → * ox ≡ x → nat→ω (ω→nato ltd) ≡ x | |
139 ind1 {o∅} iφ refl = sym o∅≡od∅ | |
140 ind1 (isuc {x₁} ltd) ox=x = begin | |
141 nat→ω (ω→nato (isuc ltd) ) | |
142 ≡⟨⟩ | |
143 Union (nat→ω (ω→nato ltd) , (nat→ω (ω→nato ltd) , nat→ω (ω→nato ltd))) | |
144 ≡⟨ cong (λ k → Union (k , (k , k ))) lemma ⟩ | |
145 Union (* x₁ , (* x₁ , * x₁)) | |
146 ≡⟨ trans ( sym *iso) ox=x ⟩ | |
147 x | |
148 ∎ where | |
149 open ≡-Reasoning | |
150 lemma0 : x ∋ * x₁ | |
151 lemma0 = subst (λ k → odef k (& (* x₁))) (trans (sym *iso) ox=x) (λ not → not | |
152 (& (* x₁ , * x₁)) ⟪ pair2 , subst (λ k → odef k (& (* x₁))) (sym *iso) pair1 ⟫ ) | |
153 lemma1 : infinite ∋ * x₁ | |
154 lemma1 = subst (λ k → odef infinite k) (sym &iso) ltd | |
155 lemma3 : {x y : Ordinal} → (ltd : infinite-d x ) (ltd1 : infinite-d y ) → y ≡ x → ltd ≅ ltd1 | |
156 lemma3 iφ iφ refl = HE.refl | |
157 lemma3 iφ (isuc {y} ltd1) eq = ⊥-elim ( ¬x<0 (subst₂ (λ j k → j o< k ) &iso eq (c<→o< (ω-∈s (* y)) ))) | |
158 lemma3 (isuc {y} ltd) iφ eq = ⊥-elim ( ¬x<0 (subst₂ (λ j k → j o< k ) &iso (sym eq) (c<→o< (ω-∈s (* y)) ))) | |
159 lemma3 (isuc {x} ltd) (isuc {y} ltd1) eq with lemma3 ltd ltd1 (ω-prev-eq (sym eq)) | |
160 ... | t = HE.cong₂ (λ j k → isuc {j} k ) (HE.≡-to-≅ (ω-prev-eq eq)) t | |
161 lemma2 : {x y : Ordinal} → (ltd : infinite-d x ) (ltd1 : infinite-d y ) → y ≡ x → ω→nato ltd ≡ ω→nato ltd1 | |
162 lemma2 {x} {y} ltd ltd1 eq = lemma6 eq (lemma3 {x} {y} ltd ltd1 eq) where | |
163 lemma6 : {x y : Ordinal} → {ltd : infinite-d x } {ltd1 : infinite-d y } → y ≡ x → ltd ≅ ltd1 → ω→nato ltd ≡ ω→nato ltd1 | |
164 lemma6 refl HE.refl = refl | |
165 lemma : nat→ω (ω→nato ltd) ≡ * x₁ | |
166 lemma = trans (cong (λ k → nat→ω k) (lemma2 {x₁} {_} ltd (subst (λ k → infinite-d k ) (sym &iso) ltd) &iso ) ) ( prev {* x₁} lemma0 lemma1 ) | |
167 | |
168 ω→nat-iso : {i : Nat} → ω→nat ( nat→ω i ) (ω∋nat→ω {i}) ≡ i | |
169 ω→nat-iso {i} = lemma i (ω∋nat→ω {i}) *iso where | |
170 lemma : {x : Ordinal } → ( i : Nat ) → (ltd : infinite-d x ) → * x ≡ nat→ω i → ω→nato ltd ≡ i | |
171 lemma {x} Zero iφ eq = refl | |
172 lemma {x} (Suc i) iφ eq = ⊥-elim ( ωs≠0 (nat→ω i) (trans (sym eq) o∅≡od∅ )) -- Union (nat→ω i , (nat→ω i , nat→ω i)) ≡ od∅ | |
173 lemma Zero (isuc {x} ltd) eq = ⊥-elim ( ωs≠0 (* x) (subst (λ k → k ≡ od∅ ) *iso eq )) | |
174 lemma (Suc i) (isuc {x} ltd) eq = cong (λ k → Suc k ) (lemma i ltd (lemma1 eq) ) where -- * x ≡ nat→ω i | |
175 lemma1 : * (& (Union (* x , (* x , * x)))) ≡ Union (nat→ω i , (nat→ω i , nat→ω i)) → * x ≡ nat→ω i | |
176 lemma1 eq = subst (λ k → * x ≡ k ) *iso (cong (λ k → * k) | |
177 ( ω-prev-eq (subst (λ k → _ ≡ k ) &iso (cong (λ k → & k ) (sym | |
178 (subst (λ k → _ ≡ Union ( k , ( k , k ))) (sym *iso ) eq )))))) | |
179 |